1993
DOI: 10.1002/jbm.820270110
|View full text |Cite
|
Sign up to set email alerts
|

Extensive porosity at the cement–femoral prosthesis interface: A preliminary study

Abstract: This study is the first description of the extensive porosity which is preferentially located at the cement-prosthesis interface of cemented femoral components of total hip replacements. The observation is important because the interfacial porosity may decrease the strength of the cement-femoral prosthesis interface and jeopardize the mechanical integrity of the cement mantle. We examined the cement-metal interfaces from a multiplicity of in vivo and in vitro specimens using both optical and scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 8 publications
4
69
0
1
Order By: Relevance
“…In addition, subsidence may be promoted by cement-stem interfacial porosity which can be as much as 50%, even when advanced mixing procedures are used. 17 Obviously, cement cracks may allow substantial subsidence. The effects of creep on the cement stresses were analysed by considering the maximal and average cement stress values.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, subsidence may be promoted by cement-stem interfacial porosity which can be as much as 50%, even when advanced mixing procedures are used. 17 Obviously, cement cracks may allow substantial subsidence. The effects of creep on the cement stresses were analysed by considering the maximal and average cement stress values.…”
Section: Discussionmentioning
confidence: 99%
“…Davies and Hams (1995) showed that porosity reduction by centrifugation did not change the linear dimensions of Simplex P cement and subsequently suggested that linear shrinkage was more important than volumetric shrinkage for fixation of the implant. Several studies have also revealed that extensive porosity is aggregated at the cement-stem interface in retrieved cement mantle and laboratory-prepared specimens (Jasty et al 1991, James et al 1993, Bishop et al 1996. This aggregation of pores could influence the interface bonding between the stem and the cement.…”
mentioning
confidence: 99%
“…6,7 These maneuvers, however, do not diminish pores at the cement-stem interface. 9 The porosity at the interface has been attributed to several factors, such as rheological characteristics of the cement, monomer evaporation, and cement shrinkage. 9,14 In this study, we observed that both precooling the bone and preheating the stem could achieve porosity reduction at the cement-stem interface.…”
Section: Discussionmentioning
confidence: 99%
“…9 The porosity at the interface has been attributed to several factors, such as rheological characteristics of the cement, monomer evaporation, and cement shrinkage. 9,14 In this study, we observed that both precooling the bone and preheating the stem could achieve porosity reduction at the cement-stem interface. We believe that cement shrinkage during polymerization plays an important role in the development of interfacial porosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation